Transparency in Local Governments: A Bibliometric Analysis - GÜNEY, Cengiz; AKINCI, Abdulvahap (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study presents the importance of transparency in local governments and a bibliometric analysis of academic studies in this field. Transparency is a fundamental principle that increases the accountability of local governments, provides citizens with access to information and strengthens participatory democracy. In the study, academic studies in the Web of Science database examining the issue of transparency in local governments were analyzed. As a result of the analysis, it was determined that the first works were published in 1997 and reached the highest level in 2020, but there was a decrease in the number of publications after 2020. It has been observed that articles are dominant in the literature and fields such as political science, management and economics stand out. Studies focusing on SSCI and ESCI indexes have been frequently published by the Universities of Minho, Granada and London. The works are generally published in English and Spanish and have been published by major publishing houses such as Taylor & Francis, Elsevier and Sage. Contributions were made from more than 90 countries, especially Spain, America and England. Additionally, it has been determined that research focuses on sustainable development goals such as quality education and reducing inequalities.